Catalytic Asymmetric Addition of Meldrum's Acid, Malononitrile, and 1, 3‐Dicarbonyls to ortho‐Quinone Methides Generated In Situ Under Basic Conditions. Issue 16 (12th March 2015) - Caruana, Lorenzo; Mondatori, Martina; Corti, Vasco; Morales, Sara; Mazzanti, Andrea; Fochi, Mariafrancesca; Bernardi, Luca
Abstract A new approach to the utilization of highly reactive and unstable ortho‐quinone methides (o‐QMs) in catalytic asymmetric settings is presented. The enantioselective reactions are catalysed by bifunctional organocatalysts, and the o‐QM intermediates are formed in situ from 2‐sulfonylalkyl phenols through base‐promoted elimination of sulfinic acid. The use of mild Brønsted basic conditions for transiently generating o‐QMs in catalytic asymmetric processes is unprecedented, and allows engaging productively in the reactions nucleophiles such as Meldrum's acid, malononitrile and 1, 3‐dicarbonyls. The catalytic transformations give new and general entries to 3, 4‐dihydrocoumarins, 4H‐chromenes and xanthenones. These frameworks are recurring structures in natural product and medicinal chemistry, as testified by the formal syntheses of (R)‐tolterodine and (S)‐4‐methoxydalbergione from the catalytic adducts.